KAIDAH KEBAHASAAN DALAM TEKS KUMPULAN PANTUN ADAT MELAYU SAMBAS KARYA NAHARI - Hakim, Lukman Nul; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the elements of linguistic rules that build the pantun text, see and know the forms of tradition and culture in the Sambas Malay community which is reflected in the pantun text. The general problem in this study is